PHYSICAL QUALITY OF BALI CATTLE SUB PRIMAL CARCASS AT DIFFERENT MUSCLE LOCATIONS - A. A., Sastra; Sriyani, N. L. P.; Putra, I G. A. A. (Jurnal Peternakan Tropika, 2023)
This study aims to determine the physical quality of meat at the location of muscles that move passively represented by tender loin, semi-active in the sub primal carcass round, and very active hind shank. The research took place at the Laboratory of Animal Products technology and Microbiology, Faculty of Animal Husbandry, Udayana University. The sampling was carried out at Mambal slaughter house. The research was carried out for three months starting from May – July 2021 from preparation to data analysis. A Completely Randomized Design with three treatments for different muscle locations. Each Treatment Consisted of seven replications, the treatments were as follows: P1: passive muscle was represented by sub primal carcass tender loin, P2: semi-active muscle was represented by sub primal carcass round, P3: active muscle was represented by sub primal carcass hind shank. The results showed that the physical quality of the sub primal carcass of bali cattle at different muscle locations had a significant effect (P<0,05) on pH, colour, water holding capacity, raw sharinkage and had no significant effect (P>0,05) on sharinkage cook. The conclusion of this study is that the results of the analysis of pH values, colour, water holding capacity, and raw losses of Balinese beef were significant different white the cooking losses of Balinese beef were not significantly different. Keywords: physical quality, bali beef, differences in muscle locations